2016
DOI: 10.1161/jaha.115.002531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nitrate Use on Survival in Acute Heart Failure: A Propensity‐Matched Analysis

Abstract: BackgroundThere is limited evidence that the use of nitrates in acute decompensated heart failure early after presentation to a hospital can improve clinical outcomes. We aimed to determine whether early nitrate exposure is associated with improved survival in a large retrospective cohort study.Methods and ResultsWe examined 11 078 acute decompensated heart failure patients who presented to emergency departments in Ontario, Canada, between 2004 and 2007, in the Enhanced Feedback For Effective Cardiac Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Hospitalization was reported in six studies. 24,28,30,33,36,40 A high heterogeneity between studies was found. Therefore, the random-effects model was used.…”
Section: Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalization was reported in six studies. 24,28,30,33,36,40 A high heterogeneity between studies was found. Therefore, the random-effects model was used.…”
Section: Hospitalizationmentioning
confidence: 99%
“…23 Several studies have compared nitrates with control treatments for HF, but no consistent outcomes have been reported. [24][25][26][27][28][29][30][31][32][33][34][35][36] Therefore, this meta-analysis was conducted to assess the efficacy and safety of nitrates compared with control treatment for HF.…”
Section: Introductionmentioning
confidence: 99%
“…It is significant that a significantly lower dose of nitrates than is used in clinical practice was used in the mentioned study. Although nitrates are used very often, no study has shown a reduction in mortality due to the use of nitrates [84][85][86]. One of the potential limitations of using nitrates is their propensity for tachyphylaxis [87,88].…”
Section: Vasodilators 711 Nitratesmentioning
confidence: 99%
“…It is significant that a significantly lower dose of nitrates than is used in clinical practice was used in the mentioned study. Although nitrates are used very often, no study has shown a reduction in mortality due to the use of nitrates [90][91][92]. One of the potential limitations of using nitrates is their propensity for tachyphylaxis [93,94].…”
Section: Nitratesmentioning
confidence: 99%